2014
DOI: 10.1016/j.jpeds.2013.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Justifying Domestic Violence Predict Endorsement of Corporal Punishment and Physical and Psychological Aggression towards Children: A Study in 25 Low- and Middle-Income Countries

Abstract: Objective The Convention on the Rights of the Child has prompted countries to protect children from abuse and exploitation. Exposure to domestic violence and corporal punishment are risk factors in children’s development. This study investigated how women’s attitudes about domestic violence are related to attitudes about corporal punishment, and harsh behaviors toward children, and whether country-wide norms regarding domestic violence and corporal punishment are related to psychological aggression and physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 10 publications
4
52
1
Order By: Relevance
“…To our knowledge, only three cross-national studies have examined a societal-level risk factor using child maltreatment data collected from surveys. Two studies used Multiple Indicator Cluster Survey (MICS) data from 25 middle and lower income countries and found that past-month caregiver reported child physical and psychological abuse was higher in countries where violence in families was more of a cultural norm (i.e., they reported greater acceptance of corporal punishment and intimate partner violence; Lansford et al 2014) and in countries with lower levels of education (Lansford and Deater-Deckard 2012). The third study utilized data from 28 countries reporting childhood trauma questionnaire (CTQ) scores, which asks children 12 and over to rate the frequency that events related to child abuse and neglect occurred when they “were growing up” (Viola et al 2016).…”
mentioning
confidence: 99%
“…To our knowledge, only three cross-national studies have examined a societal-level risk factor using child maltreatment data collected from surveys. Two studies used Multiple Indicator Cluster Survey (MICS) data from 25 middle and lower income countries and found that past-month caregiver reported child physical and psychological abuse was higher in countries where violence in families was more of a cultural norm (i.e., they reported greater acceptance of corporal punishment and intimate partner violence; Lansford et al 2014) and in countries with lower levels of education (Lansford and Deater-Deckard 2012). The third study utilized data from 28 countries reporting childhood trauma questionnaire (CTQ) scores, which asks children 12 and over to rate the frequency that events related to child abuse and neglect occurred when they “were growing up” (Viola et al 2016).…”
mentioning
confidence: 99%
“…al. 14 In our study unfortunately some of the children admitted that their mothers were also the victims of domestic violence. In a study carried out in some middle and low-income countries, mothers who justify partner violence towards themselves were more likely to believe that corporal punishment is necessary to discipline children 15 .…”
Section: Discussionmentioning
confidence: 66%
“…These findings revealed that patriarchal ideology still tightly controls Cambodian society. Both men and women still think violence can be justified because women should respect men [36] [38] [39]. The women were silent because they were afraid to break the social norms [44] [45].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, study in Pakistan found that a majority of women remained silent because they think they are weak, and out of respect for husbands and the elderly in the family [38]. Another survey study in 25 low and middle income countries indicated wives believed that domestic violence against women was appropriate and necessary in some circumstances [39]. Such justification does not only allow domestic violence against women to occur, but also on children, which teach them to absurd violence as a mean to have the upper hand on any decision in life.…”
Section: Literature Reviewmentioning
confidence: 99%